Comparison of properties of polypropylene fiber glass in injection moulding process using different gate locations - Balai, Lorita Lawi (2018)
This project investigates the mechanical properties of polypropylene filled with fiber glass in injection molding process using single and twin gate locations. The objective of this study is to compare the mechanical properties of polypropylene filled with fiberglass having the difference gate location injected by injection molding machine using Taguchi method. The investigated mechanical properties were tensile strength, modulus strength and percentage of elongation. The effect melt temperature, holding pressure, injection time and cooling time on the mechanical properties of the material were studied. L9 orthogonal arrays with 3 replications were done with 27 totals of specimens for each gate location. The result collected was optimized using Taguchi method and P-value and R-square were calculated using analysis of variance (ANOVA). According to the result analysis, it is found that single gate location shows good in tensile strength and percentage of elongation. The significant factors that affected the tensile strength are cooling time, injection time, holding pressure and melt temperature .The significant factors that affected the percentage of elongation is melt temperature followed by cooling time, holding pressure and injection time. Meanwhile, twin gate location shows the highest modulus of strength. The significant factors that affected the modulus strength are cooling time, melt temperature, holding pressure and injection time . Thus, this result shows that in twin gate location, fiberglass in polypropylene melt penetrate in between gate location, as result modulus strength in twin gate greater then single gate. Meanwhile, in single gate location, one-way flow of fiber glass in dumbbell test specimen which resulted the tensile strength and percentage of elongation higher than twin gate location.